SYNTHESIS AND ANTIMICROBIAL ACTIVITY OF NOVEL FUSED PYRAZOLES - Gurunanjappa, Pavithra; Nagamallu, Renuka; Kariyappa, Ajay Kumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objective: The aim of the present work was to synthesize fused pyrazoles and examine them for their in vitro antimicrobial activity. Methods: The formyl pyrazoles were synthesized by Vilsmeierâ€“Haack reaction from o-hydroxy acetophenone hydrazones. The pyrazoles on oxidative cyclisation in the presence of ethanol and catalytic amount of H2SO4 yielded pyrano [4,3-c] pyrazoles. The structures of the synthesized derivatives were confirmed by Mass, 1H NMR and elemental analysis. The synthesized new pyranopyrazoles were screened for their antimicrobial activity by broth dilution technique. Results: The results of the antimicrobial assay revealed that the compound 4b having chloro substitution showed good activity against different microorganisms tested. Conclusion: It is noteworthy that the compounds synthesized by a simple and accessible procedure leads to a molecules of promising antimicrobial activity. Â